The Development of a Novel, Standards-Based Core Curriculum for Community Facing, Clinic-Based Community Health Workers - George, Sheba; Silva, Lucero; Llamas, Myra; Ramos, Irma; Joe, Justin; Mendez, Juan; Salazar, Rosalva; Tehan, Jim; Vasquez, Tatiana; Nealy, Schetema; Balcazar, Hector (Frontiers in Public Health, 2021)
Introduction: Historically, CHW trainings have been developed to support community-based CHWs. When CHWs have been trained to engage with patients, typically such trainings have been for short term grant funded projects, focusing on a specific health intervention and not for long term, ongoing engagement of CHWs employed in clinical settings. To the best of our knowledge, this is the first such effort to describe the development of a standards-based training curriculum for clinic-based CHWs using a novel conceptual framework. Methods: Our conceptual approach for curricular development has several innovative features including: 1) a foundational consultation process with CHW national experts to inform curricular development approach, process and content; 2) utilization of the CHW Consensus Project (C3 Project) to provide curricular standards and guide learning objectives; 3) integration of three key stakeholder group perspectives (patients, healthcare teams and healthcare systems); 4) use of popular education principles, aiming to foster a collaborative learning process; 5) integration of adult learning principles which build on learners’ experiences, culminating in a modified apprenticeship model and 6) collaboration with clinical partners throughout planning and development of the curriculum. Results: The resulting standards-based curriculum is comprised of ten modules, which span three areas of focus: 1) Establishing a professional CHW identity and competencies; 2) Outlining the context, processes and key actors in health care settings with whom CHWs will engage; and 3) Identifying the main forces that shape health and health care outcomes of patients/families and communities. Discussion: We highlight four lessons from our curriculum development process that may help other such efforts. First, curricular development should utilize CHW standards, existing training materials, and community-focused principles to inform curricular content and learning outcomes. Second, curricula should support training delivery using experience-based, participatory approaches, consistent with adult education and popular education principles. Third, training development for clinical settings should also draw from clinical CHW experiences and input. Fourth, curricula should support training for key stakeholders and champions in clinical organizations to improve organizational readiness for integrating CHWs into healthcare teams and health systems. Our results contribute to growing research on effective CHW training methods for clinical settings.